CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, and preparation method and application thereof

CN122999209APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611169601.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]针对现有活性炭负载金属活性组分的低温脱除NOx和CO活性较差,对NOx和CO脱除率低等问题,本发明提出一种低温催化氧化CO与还原NO的CuCoCe/AC催化剂及其制备方法与应用,以廉价的椰壳活性炭AC为载体,通过硝酸活化预处理-柠檬酸络合浸渍法-等离子体表面处理-水蒸气协同焙烧活化-低温臭氧表面改性将金属活性组分Cu、Co、Ce负载到AC上制得CuCoCe/AC催化剂,实现在100-250℃条件下CO和NO同步脱除

Benefits of technology

(1)本发明低温氧化CO与还原NO的CuCoCe/AC催化剂在100~250℃低温区间兼具优异的氧化CO与还原NO协同脱除活性,有效克服了现有活性炭负载金属催化剂在低温下脱除NOx与CO时活性不足、效率偏低的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999209A_ABST
    Figure CN122999209A_ABST
Patent Text Reader

Abstract

The application relates to a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO and a preparation method and application thereof, and belongs to the technical field of flue gas purification. The CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO takes coconut shell activated carbon AC as a carrier, and active components CuO, Co2O3 and CeO2 are loaded on the coconut shell activated carbon AC; the total mass of Cu, Co and Ce elements in the active components accounts for 4-6% of the AC, the total mass of Co and Ce elements accounts for 2-3% of the AC, and the mole amount of Co accounts for 20-80% of the total mole amount of Co and Ce, taking the total mole amount of Co and Ce as 100%. The CuCoCe / AC catalyst is prepared through nitric acid activation pretreatment-lime acid complex impregnation-plasma surface treatment-water vapor synergistic calcination activation-low-temperature ozone surface modification to load Cu, Co and Ce on the AC, so that low-temperature CO and NO are synchronously removed. The CuCoCe / AC catalyst has the characteristics of developed pore structure and uniformly dispersed active components, has high NO and CO removal efficiency, and is environment-friendly and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, its preparation method and application, belonging to the field of flue gas purification technology. Background Technology

[0002] Currently, efforts are underway to eliminate NO from sintering flue gas. x Commonly used technologies for CO and NO reduction are CO selective catalytic reduction (CO-SCR) and CO selective catalytic oxidation (CO-SCO). Among these, CO-SCR technology can separate CO and NO. x Simultaneous removal and conversion of CO2 and N2, while CO-SCO is suitable for treating low-concentration CO, boasting advantages such as low reaction temperature and high oxidation efficiency, making it one of the most economical and efficient emission reduction technologies. If CO-SCR and CO-SCO technologies can be applied synergistically, it is possible to treat waste with waste and eliminate secondary pollution.

[0003] To achieve the synergistic application of CO-SCR and CO-SCO technologies, it is necessary to develop technologies that combine NO... x A composite catalyst with dual functionalities of selective reduction and CO catalytic oxidation comprises a porous support and a highly efficient active component. Unmodified activated carbon supports suffer from limitations due to microporous mass transfer resistance and insufficient surface active sites, resulting in poor dispersion of active metals and unsatisfactory CO and NO removal. Existing composite catalysts for the synergistic removal of NO and CO are primarily inhibited by O2, SO2, and H2O in the flue gas. O2 preferentially oxidizes CO, leading to insufficient reducing agent; H2O competes for adsorption active sites; and SO2 causes sulfation and deactivation of active metals. Furthermore, the catalysts suffer from insufficient long-term stability and easy loss of active components, limiting their industrial applications. Summary of the Invention

[0004] Low-temperature NO removal using existing activated carbon-supported metal active components x It has poor activity with CO and is less effective against NO. x To address issues such as low CO removal rates, this invention proposes a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, along with its preparation method and applications. Using inexpensive coconut shell activated carbon (AC) as a support, the metal active components Cu, Co, and Ce are loaded onto AC via nitric acid activation pretreatment, citric acid complexation impregnation, plasma surface treatment, steam co-calcination activation, and low-temperature ozone surface modification to obtain the CuCoCe / AC catalyst. This achieves simultaneous removal of CO and NO at 100-250℃. The CuCoCe / AC catalyst of this invention features a well-developed pore structure, uniform dispersion of active components, high CO removal efficiency, and is environmentally friendly and pollution-free.

[0005] A low-temperature catalytic oxidation of CO and reduction of NO CuCoCe / AC catalyst is provided, using coconut shell activated carbon AC as a support. The active components CuO, Co2O3 and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co and Ce elements in the active components accounts for 4-6% of AC, of ​​which the total mass of Co and Ce elements accounts for 2-3% of AC. Based on the total molar mass of Co and Ce as 100%, the molar mass of Co accounts for 20-80%.

[0006] The specific steps for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 60~80℃ for ultrasonic treatment for 2~4h, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to the nitric acid solution for surface activation treatment, solid-liquid separation, and washed with deionized water until the pH of the washing solution was 6-8. The activated coconut shell activated carbon AC was obtained by drying and was denoted as HNO3 / AC. (3) Add activated coconut shell activated carbon AC to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnate at 80~90℃ for 2~4h, then let it stand at room temperature for 24~36h, and vacuum dry to obtain CuCoCe / AC precursor; (4) Plasma-modified CuCoCe / AC precursor was obtained by plasma surface treatment of CuCoCe / AC precursor; (5) The plasma-modified CuCoCe / AC precursor is heated at a constant rate to 500~600℃ and steam is introduced for co-calcination activation for 30~40 min. The temperature is then reduced to 100~120℃ and ozone is introduced for surface modification for 30~40 min to obtain CuCoCe / AC catalyst.

[0007] Preferably, in step (2), the concentration of the nitric acid solution is 4~6 mol / L, the surface activation treatment temperature is 80~90℃, and the time is 2~3h.

[0008] Preferably, in the mixed solution of step (3), the concentration of citric acid is 0.48~0.50 mol / L, the concentration of copper nitrate is 0.31~0.47 mol / L, the concentration of cobalt nitrate is 0.025~0.252 mol / L, and the concentration of cerium nitrate is 0.05~0.15 mol / L.

[0009] Preferably, in step (4), the plasma surface treatment power is 300~330W, the time is 20~30min, and the plasma discharge gas is a hydrogen-nitrogen mixture.

[0010] More preferably, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture is 1~2:10, and the flow rate of the hydrogen-nitrogen mixture is 13~15 mL / min.

[0011] Preferably, the uniform heating rate in step (5) is 10~20℃ / min.

[0012] Preferably, in step (5), the water vapor rate is 30~50 mL / min and the ozone rate is 20~40 mL / min.

[0013] The application of the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO in low-temperature catalytic oxidation of CO and reduction of NO: the catalytic temperature is 100~250℃.

[0014] The present invention provides a method for testing the CO and NO removal performance of the CuCoCe / AC catalyst: (1) Purge the CuCoCe / AC catalyst with N2 and set the temperature rise rate of the fixed bed reactor to 10℃ / min, so that the temperature of the fixed bed reactor for removing CO+NO rises to 100℃; (2) The mixed gas (simulated sintering flue gas) to be desorbed from CO and NO is fed into a fixed-bed reactor, and the reaction temperature is controlled at 100-250℃. In the mixed gas (simulated sintering flue gas) to be desorbed from CO and NO, the volume of NO accounts for 0.24% of the mixed flue gas, the volume of O2 accounts for 10%, the volume of CO accounts for 0.4%, and N2 is the equilibrium gas. The total flow rate of the mixed gas is 1000 ml·min. -1 (1×10 6 (ppm), CO+NO in flue gas is oxidized to CO2 and reduced to N2 gas by different CuCoCe / AC catalysts; (3) Before and after the process of removing CO+NO from the mixed gas by different CuCoCe / AC catalysts, the gas analyzer recorded the various components in the mixed gas and calculated the efficiency of CO and NO removal. (4) The gas after the reaction is released into the atmosphere after the unreacted CO and NO are absorbed by the limestone solution.

[0015] The principle of using the CuCoCe / AC catalyst of this invention for the low-temperature catalytic removal of CO and NO from flue gas is as follows: This invention utilizes coconut shell activated carbon pretreated with nitric acid as a carrier, combining chemical modification and physical regulation to effectively improve the dispersibility, anti-sintering properties, and selective adsorption capacity of active components. It is also simple to operate and has a wide range of applications. Citric acid complexation impregnation improves the dispersibility of Cu, Co, and Ce elements on the catalyst surface, effectively inhibiting metal grain agglomeration and significantly enhancing the catalyst's activity and stability. The process is simple and easy to control. Plasma surface treatment can significantly improve the efficiency of NO removal and CO oxidation and broaden the low-temperature activity window by constructing high-activity sites, introducing surface defects and functional groups. It also enhances the catalyst's resistance to poisoning and structural stability, thereby extending its lifespan. Its service life; the co-calcination activation energy of steam significantly improves the low-temperature activity and stability of the catalyst, reduces the reaction temperature, optimizes surface oxygen species, enhances anti-sintering ability, and improves CO and NO removal efficiency; low-temperature ozone oxidation selectively introduces active functional groups such as carboxyl and phenolic hydroxyl groups under mild conditions without destroying the pore structure of activated carbon, achieving precise control of surface chemical properties; the CuCoCe / AC catalyst of this invention uses AC as the framework structure and reactant enrichment platform, constructs a bifunctional catalyst by combining Cu, Co and Ce reaction sites, and realizes the coupling of CO catalytic oxidation and NO catalytic reduction reactions, which can simultaneously and efficiently remove CO and NO, achieving environmental protection and pollution-free results.

[0016] The beneficial effects of this invention are: (1) The CuCoCe / AC catalyst for low-temperature oxidation of CO and reduction of NO of the present invention has excellent synergistic removal activity of CO oxidation and NO reduction in the low temperature range of 100~250℃, which effectively overcomes the problem of insufficient activity and low efficiency of existing activated carbon supported metal catalysts when removing NOx and CO at low temperature. (2) The present invention uses coconut shell activated carbon pretreated with nitric acid as a carrier, which has the dual effects of chemical modification and physical regulation. It can effectively improve the dispersibility, anti-sintering and selective adsorption capacity of active components, and is simple to operate and has a wide range of applications. Citric acid complex impregnation method can improve the dispersibility of Cu, Co and Ce elements on the catalyst surface, effectively inhibit metal grain agglomeration, significantly improve the activity and stability of the catalyst, and the process is simple and easy to control. Plasma surface treatment can greatly improve the denitrification efficiency and broaden the low temperature activity window by constructing high active sites, introducing surface defects and functional groups, and can also enhance the catalyst's anti-poisoning ability and structural stability, thereby extending its service life. Water vapor activation can significantly improve the low temperature activity and stability of the catalyst, reduce the reaction temperature, optimize surface oxygen species, enhance anti-sintering ability, and improve CO and NO removal efficiency. Low temperature ozone oxidation selectively introduces active functional groups such as carboxyl and phenolic hydroxyl groups under mild conditions without destroying the pore structure of activated carbon, and achieves precise control of surface chemical properties. (3) The present invention couples the CO-SCR and CO-SCO processes, which can simultaneously remove CO and NO at low temperatures.x It is converted into CO2 and N2, and has high CO oxidation efficiency. This technical route meets the requirements of green environmental protection, realizes the synergistic treatment and resource utilization of waste gas, and provides a theoretical basis for the development of low-temperature high-efficiency bifunctional catalysts. Attached Figure Description

[0017] Figure 1 The graphs show the CO and NO removal curves of the CuCoCe / AC catalysts in Examples 1-3. Figure 2 SEM images of CuCoCe / AC catalysts from Examples 1-3; Figure 3 The figures show the nitrogen isothermal adsorption-desorption curves of CuCoCe / AC catalysts in Examples 1-3. Figure 4 XRD patterns of CuCoCe / AC catalysts in Examples 1-3; Figure 5 The images show the FTIR spectra of CuCoCe / AC catalysts in Examples 1-3. Detailed Implementation

[0018] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the content described.

[0019] In this embodiment of the invention, the catalytic reactor is a fixed-bed reactor. The feed gas is preheated before entering the reactor, the reaction temperature is 100~250℃, the total gas flow rate is 1000ml / min, and the GHSV is 30000h. -1 ; The simulated sintering flue gas composition is as follows: NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10% of the volume, CO accounts for 0.4% of the volume, and N2 is the balance gas. The simulated sintering flue gas is mixed and fed into a fixed bed reactor with a temperature rise rate of 10℃ / min. The gas flow rate is controlled by a rotor flow meter. The purity of CO, NO, N2, and O2 used in this invention is 99.99%. The activity of the catalyst in removing CO and NO was evaluated using CO conversion and NO conversion rates, calculated as follows: ; ; In the formula: ------CO concentration at reactor inlet, ppm; -----Reactor outlet CO concentration, ppm; ------NO concentration at reactor inlet, ppm; -----NO concentration at reactor outlet, ppm; The CuCoCe / AC series catalysts for low-temperature catalytic oxidation of CO and reduction of NO in this invention have a catalyst structure with coconut shell activated carbon AC as the support and CuO, Co2O3 and CeO2 as active components.

[0020] Example 1: This example describes a CuCoCe / AC catalyst for the low-temperature catalytic oxidation of CO and reduction of NO. Coconut shell activated carbon AC is used as the support. The active components CuO, Co2O3, and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co, and Ce in the active components accounts for 4% of AC, with Co and Ce accounting for 2% of AC. Assuming the total molar mass of Co and Ce is 100%, the molar mass of Co is 20%, denoted as catalyst CuCo. 0.2 Ce 0.8 / AC; A method for preparing a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, the specific steps of which are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 60°C for 2 hours for ultrasonic treatment, solid-liquid separation, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to a nitric acid solution with a concentration of 4 mol / L and surface activated at 80℃ for 2 h. After solid-liquid separation, the activated coconut shell activated carbon AC was obtained by washing with deionized water until the pH of the washing solution was 7 and then dried. It was denoted as HNO3 / AC. (3) Activated coconut shell carbon AC was added to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnated at 80°C for 2 hours, then placed at room temperature for 24 hours and vacuum dried to obtain CuCoCe / AC precursor; the concentration of citric acid in the mixed solution was 0.48 mol / L, the concentration of copper nitrate was 0.31 mol / L, the concentration of cobalt nitrate was 0.1 mol / L and the concentration of cerium nitrate was 0.025 mol / L. (4) The CuCoCe / AC precursor was subjected to plasma surface treatment to obtain plasma-modified CuCoCe / AC precursor; the plasma surface treatment power was 300W, the time was 20min, the plasma discharge gas was a hydrogen-nitrogen mixture, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture was 1:10, and the flow rate of the hydrogen-nitrogen mixture was 13mL / min. (5) The plasma-modified CuCoCe / AC precursor was heated to 500℃ at a heating rate of 10℃ / min, and water vapor was introduced at a rate of 13mL / min for 30min to co-calcine and activate it. The temperature was then reduced to 100℃ and ozone (ozone rate of 20mL / min) was introduced for surface modification for 30min to obtain CuCoCe / AC catalyst. This embodiment describes the low-temperature catalytic oxidation of CO and the reduction of NO using CuCo. 0.2 Ce 0.8 The AC catalyst was used to remove CO and NO at 100~250℃, with a catalyst loading of 8g. Before the experiment, N2 was introduced into the fixed-bed reactor to purge other gases and avoid interference. Then, CO and NO from simulated sintering flue gas were introduced for 1 hour to allow CuCo to react. 0.2 Ce 0.8 / AC catalyst adsorption saturates CO+NO, reducing experimental error; The simulated total gas flow rate is 1000 ml / min, and the GHSV is 30000 h. -1 NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10%, CO accounts for 0.4%, and N2 is the equilibrium gas. The simulated sintering gases are mixed in a mixing chamber and then fed into a fixed-bed reactor. 0.2 Ce 0.8 Under the action of AC catalyst, CO is oxidized to CO2 and NO is reduced to N2; the remaining CO and NO in the gas after the reaction are absorbed by limestone solution and then discharged into the atmosphere. The CO and NO concentrations at the inlet and outlet are detected by flue gas analyzer. CuCo 0.2 Ce 0.8 The CO+NO removal efficiency of the AC catalyst is shown in Table 1 and... Figure 1 , Table 1 CuCo 0.2 Ce 0.8 / AC catalyst CO+NO removal efficiency

[0021] From Table 1 and Figure 1 It can be seen that CuCo 0.2 Ce 0.8 The CO and NO removal rates of the / AC catalyst decreased from 99.93% and 73.79% to 98.40% and 40.83% respectively at 100–250 °C. Figures 2-5Characterization results indicate that the larger specific surface area provides more active sites for NO removal, and the increased oxygen vacancies promote the adsorption and activation of reactant gases. Cu, Co, and Ce have a synergistic effect, not only generating more metal ion channels in the catalyst, but also enabling the transfer of the -Ce-O-Co- solid solution from metal ions, enhancing the electronic interactions between components, facilitating electron migration, and promoting the SCR reaction.

[0022] Example 2: This example describes a CuCoCe / AC catalyst for the low-temperature catalytic oxidation of CO and reduction of NO. Coconut shell activated carbon AC is used as the support. The active components CuO, Co2O3, and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co, and Ce in the active components accounts for 4% of AC, with Co and Ce accounting for 2% of AC. Assuming the total molar mass of Co and Ce is 100%, the molar mass of Co is 50%, denoted as catalyst CuCo. 0.5 Ce 0.5 / AC; A method for preparing a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, the specific steps of which are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 75℃ for ultrasonic treatment for 2.5h, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to a nitric acid solution with a concentration of 5 mol / L and surface activated at 85℃ for 2.5 h. After solid-liquid separation, the activated coconut shell activated carbon AC was obtained by washing with deionized water until the pH of the washing solution was 6 and then dried. It was denoted as HNO3 / AC. (3) Activated coconut shell carbon AC was added to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnated at 85°C for 3 h, then placed at room temperature for 30 h and vacuum dried to obtain CuCoCe / AC precursor; the concentration of citric acid in the mixed solution was 0.48 mol / L, the concentration of copper nitrate was 0.31 mol / L, the concentration of cobalt nitrate was 0.1 mol / L and the concentration of cerium nitrate was 0.1 mol / L. (4) The CuCoCe / AC precursor was subjected to plasma surface treatment to obtain plasma-modified CuCoCe / AC precursor; the plasma surface treatment power was 310W, the time was 25min, the plasma discharge gas was a hydrogen-nitrogen mixture, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture was 1.5:10, and the flow rate of the hydrogen-nitrogen mixture was 14mL / min; (5) The plasma-modified CuCoCe / AC precursor was heated to 550℃ at a heating rate of 15℃ / min, and activated by steam at a rate of 40mL / min for 35min. The temperature was then reduced to 110℃ and ozone (at a rate of 30mL / min) was introduced for surface modification for 35min to obtain the CuCoCe / AC catalyst. This embodiment describes the low-temperature catalytic oxidation of CO and the reduction of NO using CuCo. 0.5 Ce 0.5 The AC catalyst was used to remove CO and NO at 100~250℃, with a catalyst loading of 8g. Before the experiment, N2 was introduced into the fixed-bed reactor to purge other gases and avoid interference. Then, CO and NO from simulated sintering flue gas were introduced for 1 hour to allow CuCo to react. 0.5 Ce 0.5 / AC catalyst adsorption saturates CO+NO, reducing experimental error; The simulated total gas flow rate is 1000 ml / min, and the GHSV is 30000 h. -1 NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10%, CO accounts for 0.4%, and N2 is the equilibrium gas. The simulated sintering gases are mixed in a mixing chamber and then fed into a fixed-bed reactor. 0.5 Ce 0.5 Under the action of AC catalyst, CO is oxidized to CO2 and NO is reduced to N2; the remaining CO and NO in the gas after the reaction are absorbed by limestone solution and then discharged into the atmosphere. The CO and NO concentrations at the inlet and outlet are detected by flue gas analyzer. CuCo 0.5 Ce 0.5 The CO+NO removal efficiency of the AC catalyst is shown in Table 2. Figure 1 , Table 2 CuCo 0.5 Ce 0.5 / AC catalyst CO+NO removal efficiency

[0023] From Table 2 and Figure 1 It can be seen that CuCo 0.5 Ce 0.5 The AC catalyst maintained a CO removal rate of over 98% at 100–250 °C, but its NO removal performance was not ideal. Figures 2-5 Characterization showed that the metal oxide active components were highly dispersed on the AC support. The smaller grain size was beneficial for exposing more active sites, adsorbing and activating CO, and improving the low-temperature CO oxidation activity of the catalyst. However, since CO occupied a large number of active sites, it significantly inhibited the adsorption and activation of NO, resulting in limited catalytic NO reduction efficiency.

[0024] Example 3: This example describes a CuCoCe / AC catalyst for the low-temperature catalytic oxidation of CO and reduction of NO. Coconut shell activated carbon AC is used as the support. The active components CuO, Co2O3, and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co, and Ce in the active components accounts for 4% of AC, with Co and Ce accounting for 2% of AC. Assuming the total molar mass of Co and Ce is 100%, the molar mass of Co accounts for 80%, denoted as catalyst CuCo. 0.8 Ce 0.2 / AC; A method for preparing a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, the specific steps of which are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 80℃ for ultrasonic treatment for 4 hours, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to a nitric acid solution with a concentration of 6 mol / L and surface activated at 90°C for 3 h. After solid-liquid separation, the activated coconut shell activated carbon AC was obtained by washing with deionized water until the pH of the washing solution was 8 and then dried. It was denoted as HNO3 / AC. (3) Activated coconut shell carbon AC was added to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnated at 90°C for 4 hours, then placed at room temperature for 36 hours and vacuum dried to obtain CuCoCe / AC precursor; the concentration of citric acid in the mixed solution was 0.48 mol / L, the concentration of copper nitrate was 0.31 mol / L, the concentration of cobalt nitrate was 0.2 mol / L and the concentration of cerium nitrate was 0.05 mol / L. (4) The CuCoCe / AC precursor was subjected to plasma surface treatment to obtain plasma-modified CuCoCe / AC precursor; the plasma surface treatment power was 330W, the time was 30min, the plasma discharge gas was a hydrogen-nitrogen mixture, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture was 2:10, and the flow rate of the hydrogen-nitrogen mixture was 15mL / min. (5) The plasma-modified CuCoCe / AC precursor was heated to 600℃ at a heating rate of 20℃ / min, and activated by steam at a rate of 50mL / min for 40min. The temperature was then reduced to 120℃ and ozone (at a rate of 40mL / min) was introduced to modify the surface for 40min to obtain the CuCoCe / AC catalyst. This embodiment describes the low-temperature catalytic oxidation of CO and the reduction of NO using CuCo. 0.8 Ce 0.2The AC catalyst was used to remove CO and NO at 100~250℃, with a catalyst loading of 8g. Before the experiment, N2 was introduced into the fixed-bed reactor to purge other gases and avoid interference. Then, CO and NO from simulated sintering flue gas were introduced for 1 hour to allow CuCo to react. 0.8 Ce 0.2 / AC catalyst adsorption saturates CO+NO, reducing experimental error; The simulated total gas flow rate is 1000 ml / min, and the GHSV is 30000 h. -1 NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10%, CO accounts for 0.4%, and N2 is the equilibrium gas. The simulated sintering gases are mixed in a mixing chamber and then fed into a fixed-bed reactor. 0.8 Ce 0.2 Under the action of AC catalyst, CO is oxidized to CO2 and NO is reduced to N2; the remaining CO and NO in the gas after the reaction are absorbed by limestone solution and then discharged into the atmosphere. The CO and NO concentrations at the inlet and outlet are detected by flue gas analyzer. CuCo 0.8 Ce 0.2 The CO+NO removal efficiency of the AC catalyst is shown in Table 3. Figure 1 , Table 3 CuCo 0.8 Ce 0.2 / AC catalyst CO+NO removal efficiency

[0025] From Table 3 and Figure 1 It can be seen that CuCo 0.8 Ce 0.2 The CO and NO removal rates of the / AC catalyst decreased from 99.95% and 64.46% to 99.08% and 40.96% respectively at 100–250 °C. Figures 2-5 Characterization revealed that the catalyst surface contains abundant oxygen-containing functional groups, which can act as anchoring sites to enhance metal-support interactions, create interfacial active sites, reduce CO adsorption energy, and thus improve catalytic activity.

[0026] Example 4: This example describes a CuCoCe / AC catalyst for the low-temperature catalytic oxidation of CO and reduction of NO. Coconut shell activated carbon AC is used as the support. The active components CuO, Co2O3, and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co, and Ce in the active components accounts for 5% of AC, with Co and Ce accounting for 2.5% of AC. Based on a total molar mass of 100% for Co and Ce, the molar mass of Co accounts for 30%. A method for preparing a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, the specific steps of which are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 65℃ for ultrasonic treatment for 2.5h, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to a nitric acid solution with a concentration of 4.5 mol / L and surface activated at 82℃ for 2.2 h. After solid-liquid separation, the activated coconut shell activated carbon AC was obtained by washing with deionized water until the pH of the washing solution was 6.5 and then dried. It was denoted as HNO3 / AC. (3) Activated coconut shell carbon AC was added to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnated at 82°C for 2.5 h, then placed at room temperature for 27 h and vacuum dried to obtain CuCoCe / AC precursor; the concentration of citric acid in the mixed solution was 0.49 mol / L, the concentration of copper nitrate was 0.39 mol / L, the concentration of cobalt nitrate was 0.065 mol / L and the concentration of cerium nitrate was 0.15 mol / L. (4) The CuCoCe / AC precursor was subjected to plasma surface treatment to obtain plasma-modified CuCoCe / AC precursor; the plasma surface treatment power was 315W, the time was 22min, the plasma discharge gas was a hydrogen-nitrogen mixture, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture was 1.2:10, and the flow rate of the hydrogen-nitrogen mixture was 13.5mL / min; (5) The plasma-modified CuCoCe / AC precursor was heated to 530℃ at a heating rate of 13℃ / min, and activated by steam at a rate of 35mL / min for 33min. The temperature was then reduced to 105℃ and ozone (at a rate of 25mL / min) was introduced for surface modification for 33min to obtain the CuCoCe / AC catalyst. In this embodiment, the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO was used to remove CO and NO at 100~250℃, with a catalyst loading of 8g. Before the experiment, N2 was introduced into the fixed-bed reactor to remove other gases in the reactor and avoid interference from other gases. Then, CO and NO from simulated sintering flue gas were introduced for 1 hour to saturate the CuCoCe / AC catalyst with CO+NO adsorption and reduce experimental error. The simulated total gas flow rate is 1000 ml / min, and the GHSV is 30000 h. -1NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10%, CO accounts for 0.4%, and N2 is the equilibrium gas. The simulated sintering gas is mixed in a mixing box and then sent to a fixed-bed reactor. Under the action of CuCoCe / AC catalyst, CO is oxidized to CO2 and NO is reduced to N2. The remaining CO and NO in the gas after the reaction are absorbed by limestone solution and then discharged into the atmosphere. The CO and NO concentrations at the inlet and outlet are detected by a flue gas analyzer. The CO+NO removal efficiency of the CuCoCe / AC catalyst is shown in Table 4. Table 4 shows the CO+NO removal efficiency of the CuCoCe / AC catalyst in this embodiment.

[0027] As shown in Table 4, the CuCoCe / AC catalyst exhibits excellent low-temperature oxidation performance for CO in the temperature range of 100~250°C, while showing obvious "high-temperature inhibition" characteristics for NO. Its optimal operating temperature window is 100~130°C. Within this temperature range, the CO removal rate is maintained above 99.88%, and the NO removal rate can be maintained above 67.92%.

[0028] Example 5: This example describes a CuCoCe / AC catalyst for the low-temperature catalytic oxidation of CO and reduction of NO. Coconut shell activated carbon AC is used as the support. The active components CuO, Co2O3, and CeO2 are supported on the coconut shell activated carbon AC. The total mass of Cu, Co, and Ce in the active components accounts for 6% of AC, with Co and Ce accounting for 3% of AC. Based on a total molar mass of 100% for Co and Ce, the molar mass of Co accounts for 70%. A method for preparing a CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, the specific steps of which are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 75℃ for ultrasonic treatment for 3.5h, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to a nitric acid solution with a concentration of 5.5 mol / L and surface activated at 87°C for 2.7 h. After solid-liquid separation, the activated coconut shell activated carbon AC was obtained by washing with deionized water until the pH of the washing solution was 7.5 and then dried. It was denoted as HNO3 / AC. (3) Activated coconut shell carbon AC was added to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnated at 87°C for 3.5 h, then placed at room temperature for 33 h and vacuum dried to obtain CuCoCe / AC precursor; the concentration of citric acid in the mixed solution was 0.50 mol / L, the concentration of copper nitrate was 0.47 mol / L, the concentration of cobalt nitrate was 0.252 mol / L and the concentration of cerium nitrate was 0.108 mol / L. (4) The CuCoCe / AC precursor was subjected to plasma surface treatment to obtain plasma-modified CuCoCe / AC precursor; the plasma surface treatment power was 325W, the time was 27min, the plasma discharge gas was a hydrogen-nitrogen mixture, the volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture was 1.7:10, and the flow rate of the hydrogen-nitrogen mixture was 14.5mL / min; (5) The plasma-modified CuCoCe / AC precursor was heated to 570℃ at a heating rate of 17℃ / min, and water vapor was introduced at a rate of 45mL / min for co-calcination and activation for 37min. The temperature was then reduced to 115℃ and ozone (at a rate of 35mL / min) was introduced for surface modification for 37min to obtain the CuCoCe / AC catalyst. In this embodiment, the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO was used to remove CO and NO at 100~250℃, with a catalyst loading of 8g. Before the experiment, N2 was introduced into the fixed-bed reactor to remove other gases in the reactor and avoid interference from other gases. Then, CO and NO from simulated sintering flue gas were introduced for 1 hour to saturate the CuCoCe / AC catalyst with CO+NO adsorption and reduce experimental error. The simulated total gas flow rate is 1000 ml / min, and the GHSV is 30000 h. -1 NO accounts for 0.24% of the mixed flue gas volume, O2 accounts for 10%, CO accounts for 0.4%, and N2 is the equilibrium gas. The simulated sintering gas is mixed in a mixing box and then sent to a fixed-bed reactor. Under the action of CuCoCe / AC catalyst, CO is oxidized to CO2 and NO is reduced to N2. The remaining CO and NO in the gas after the reaction are absorbed by limestone solution and then discharged into the atmosphere. The CO and NO concentrations at the inlet and outlet are detected by a flue gas analyzer. The CO+NO removal efficiency of the CuCoCe / AC catalyst is shown in Table 5. Table 5. CO and NO removal efficiency of CuCoCe / AC catalyst in this embodiment.

[0029] As shown in Table 5, the CuCoCe / AC catalyst exhibits excellent low-temperature catalytic oxidation performance for CO in the range of 100–250°C, with a CO removal rate greater than 99.4%. However, the NO removal efficiency shows obvious high-temperature inhibition characteristics and abnormal fluctuations. The optimal operating temperature window is 100–110°C, within which the NO removal rate can be maintained above 69%.

[0030] The specific embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO, characterized in that: The CuCoCe / AC catalyst uses coconut shell activated carbon AC as a support. The active components CuO, Co2O3 and CeO2 are loaded on the coconut shell activated carbon AC. The total mass of Cu, Co and Ce elements in the active components accounts for 4~6% of AC, of ​​which the total mass of Co and Ce elements accounts for 2~3% of AC. Based on the total molar amount of Co and Ce as 100%, the molar amount of Co accounts for 20~80%.

2. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 1, characterized in that, The specific steps are as follows: (1) Coconut shell activated carbon AC was washed with deionized water, placed in a water bath at 60~80℃ for ultrasonic treatment for 2~4h, solid-liquid separation was performed, and dried to obtain pretreated coconut shell activated carbon AC. (2) The pretreated coconut shell activated carbon AC was added to the nitric acid solution for surface activation treatment, solid-liquid separation, and washed with deionized water until the pH of the washing solution was 6-8. The activated coconut shell activated carbon AC was obtained by drying and was denoted as HNO3 / AC. (3) Add activated coconut shell activated carbon AC to a mixed solution of citric acid, copper nitrate, cerium nitrate and cobalt nitrate and ultrasonically impregnate at 80~90℃ for 2~4h, then let it stand at room temperature for 24~36h, and vacuum dry to obtain CuCoCe / AC precursor; (4) Plasma-modified CuCoCe / AC precursor was obtained by plasma surface treatment of CuCoCe / AC precursor; (5) The plasma-modified CuCoCe / AC precursor is heated at a constant rate to 500~600℃ and steam is introduced for co-calcination activation for 30~40 min. The temperature is then reduced to 100~120℃ and ozone is introduced for surface modification for 30~40 min to obtain CuCoCe / AC catalyst.

3. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 2, characterized in that: Step (2) The concentration of nitric acid solution is 4~6 mol / L, the surface activation treatment temperature is 80~90℃, and the time is 2~3h.

4. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 2, characterized in that: In step (3), the concentration of citric acid in the mixed solution is 0.48~0.50 mol / L, the concentration of copper nitrate is 0.31~0.47 mol / L, the concentration of cobalt nitrate is 0.025~0.252 mol / L, and the concentration of cerium nitrate is 0.05~0.15 mol / L.

5. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 2, characterized in that: Step (4) The plasma surface treatment power is 300~330W, the time is 20~30min, and the plasma discharge gas is a hydrogen-nitrogen mixture.

6. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 5, characterized in that: The volume ratio of hydrogen to nitrogen in the hydrogen-nitrogen mixture is 1~2:10, and the flow rate of the hydrogen-nitrogen mixture is 13~15 mL / min.

7. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 2, characterized in that: Step (5) The uniform heating rate is 10~20℃ / min.

8. The method for preparing the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO according to claim 2, characterized in that: Step (5) The water vapor rate is 30~50 mL / min and the ozone rate is 20~40 mL / min.

9. The application of the CuCoCe / AC catalyst for low-temperature catalytic oxidation of CO and reduction of NO as described in claim 1 in low-temperature catalytic oxidation of CO and reduction of NO, characterized in that: The catalytic temperature is 100~250℃.